The Cold War in retrospect: a continuous international conflict or a world war? - Arie (Leo) Geronik (Cogent Social Sciences)
This essay aims to offer a new perspective on the world wars of the twentieth century and its international systems. In this context I argue that the bipolar system, in contrast to its predecessors, was not ended by a world war because this very system – or more precisely, the mode of operation derived from it, namely the Cold War – was in itself a world war. In this sense it differs from the two preceding international systems. In order to confirm this hypothesis, I will first survey the three international systems with which we are familiar from twentieth-century history, including their characteristics and legacies. I will then examine the familiar definitions of war in political- historical scholarship, propose a definition of the term ‘world war’ and finally attempt to demonstrate that the Cold War indeed falls into this category.